A preliminary examination of selected biological links between four Eastern Cape estuaries and the inshore marine environment - Vorwerk, Paul D (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2007)
The coastal transition zone (CTZ), which links the terrestrial and marine environments, has been identified as a region of high biological diversity and elevated production. Results of studies conducted in the northern hemisphere indicate that the links between estuaries and the adjacent marine environment is critical to ecological functioning within the CTZ. This study assessed the influence of selected estuaries with different hydrodynamic characteristics on the adjacent marine environment along the south-eastern coastline of southern Africa. Four estuaries were examined, including two permanently open systems, the fresh water deprived Kariega and fresh water dominated Great Fish, and two temporarily open/closed estuaries (TOCE), the Kasouga and East Kleinemonde. Results of the study indicated that outflow of estuarine water from the Great Fish Estuary contributed to a plume of less saline water being evident within the adjacent marine environment. The plume of water was associated with increased zooplankton biomass and particulate organic matter (POM) and chlorophyll-a concentrations. Adjacent to the Kariega Estuary, no evidence of fresh water outflow into the marine environment was observed. However, in the sea directly opposite the mouth of the estuary an increase in zooplankton abundance and biomass was evident. Results of numerical analyses indicated that the increase in zooplankton abundance observed adjacent to the mouth of both permanently open estuaries could not be attributed to the export of zooplankton from the estuary, but rather the accumulation of marine species within the region. The mechanisms responsible for this accumulation were not determined, but it was thought to be associated with increased food availability in the estuarine frontal zone. A similar, but less dramatic biological response was also observed in the marine environment adjacent to the two TOCEs. It is suggested that the increase in biological activity within these regions could be ascribed to seepage of estuarine or ground water through the sand bar that separates these estuaries from the sea. Results of stable carbon isotope analyses indicated that both the Great Fish and Kariega estuaries exported carbon to the nearshore marine environment. The area influenced by estuarine derived carbon was dependent on the volume of estuarine outflow to the marine environment. Adjacent to the fresh water dominated Great Fish Estuary, estuarine derived carbon was recorded up to 12km from the mouth, while adjacent to the fresh water deprived Kariega, estuarine derived carbon was only evident directly opposite the mouth. The recruitment of macrozooplankton (> 2cm) into the fresh water deprived Kariega Estuary was in the range recorded for other permanently open southern African estuaries with higher fresh water flow rates. This indicates that the mechanisms which allow estuarine dependent larvae to locate and enter estuaries are not related to fresh water inflow. In conclusion, this study has demonstrated that despite their small size relative to European and North American systems, South African permanently open and temporarily open/closed estuaries also influence biological activity within the adjacent nearshore marine environment.
Keywords: Estuaries -- South Africa -- Eastern Cape; Marine fishes -- South Africa -- Eastern Cape; Marine ecology -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape